Upaya Guru dalam Penyelesaian Problematika Pembelajaran Pendidikan Agama Islam pada Siswa Kelas X di SMA Negeri 2 Perbaungan Kabupaten Serdang Bedagai - Gultom, Nurul Fadilla; Azhar, Ihsan Satrya (Tapis: Jurnal Penelitian Ilmiah, 2023)
Education is a process of changing human attitudes and behavior to mature them through teaching and training efforts. That’s why the teachers’ role in the education world as a learning resource has become important. This study aims to reveal the learning problems of Islamic Religious Education (PAI) in class X students of SMA Negeri 2 Perbaungan, Deli Serdang Regency, and to describe the teacher's efforts in solving the problems that occurred. This case study used a qualitative research approach. Data collection techniques were observation, interviews, and documentation which were then presented in the form of a qualitative descriptive analysis to describe the conditions occurring at the research location. The researchers revealed that there were many problems experienced by teachers and students during the teaching and learning process of students at SMA Negeri 2 Perbaungan, such as students' lack of interest in reading, lack of fulfillment of learning media, lack of student concentration because there were too many students in the class. The teachers' efforts to solve these problems are making quizzes to increase students' interest in reading, dividing students into several groups to concentrate more, and creating innovative learning media to facilitate student practice activities.